High Rosmarinic Acid Content Melissa officinalis L. Phytocomplex Modulates Microglia Neuroinflammation Induced by High Glucose - Giacomina Videtta; Chiara Sasia; Nicoletta Galeotti (Antioxidants)
Diabetic patients experience hyperglycemia, which can affect multiple organs, including brain function, leading to disabling neurological complications. Hyperglycemia plays a key role in promoting neuroinflammation, the most common complication in diabetic individuals, through the activation of microglia. Attenuating hyperglycemia-related neuroinflammation in microglia may reduce diabetes-associated neurological comorbidities. Natural remedies containing phenolic compounds have shown efficacy in mitigating microglia-mediated neuroinflammation. The aim of this study was to investigate the potential of a Melissa officinalis L. (MO) phytocomplex, obtained from plant cell cultures and enriched in its main polyphenolic constituent, rosmarinic acid (RA), in attenuating hyperglycemia-induced neuroinflammation in microglia. A time-course morphological analysis of BV2 microglial cells exposed to high glucose (HG) levels showed a shift towards a proinflammatory phenotype, peaking after 48 h, which was reversed by pretreatment with MO. Biochemical assays revealed increased expression of the microglial marker CD11b (187%), activation of the NF-κB pathway (179%), expression of iNOS (225%), enhanced phosphorylation of ERK1/2 (180%), and increased expression of the proinflammatory cytokine IL-6 (173%). Pretreatment with MO prevented the aberrant expression of these proinflammatory mediators and restored SIRT1 levels. Exposure of neuronal SH-SY5Y cells to the conditioned medium from HG-exposed microglia significantly reduced cell viability. MO counteracted this effect, exhibiting neuroprotective activity. RA showed efficacy comparable to that of MO. In conclusion, MO and RA attenuated microglia-mediated oxidative imbalance and neuroinflammation under HG exposure by inhibiting the morphological shift toward a proinflammatory phenotype induced by HG and abrogating the subsequent activation of the downstream ERK1/2–NF-κB–iNOS pathway.